Understanding nonlinear behaviors of auxetic foams using X-ray tomography and pore structure analysis. (February 2022) - Du, Lamei; Luo, Sida; Xu, Ye
Abstract: With a thermo-mechanical compression process, regular polyurethane (PU) foams can transform into auxetic foams showing a negative Poisson's ratio. Using tensile tests and X-ray tomography, we investigate the structure-property relation of a series of PU foams prepared with different amount of compression treatment. We find that the Poisson's ratio decreases with the amount of compression but reaches a plateau while the maximum strain with auxetic effects keeps increasing. With pore structure analysis on the 3D tomography of those foams, the structure origin of the nonlinear mechanical behaviors is found to be closely related to the bending of ribs in the auxetic foams. We found that the Poisson's ratio is correlated with the fraction of bent ribs while the maximum auxetic strain is determined by the degree of rib bending. Our results provide insights in designing better foam-based auxetic materials for large deformation applications. Highlights: Nonlinear mechanical behaviors of a series of auxetic foams are systematically characterized. Using XCT and pore structure analysis, key structure parameters responsible for auxetic behaviors are identified. The Poisson's ratio and the maximum strain with auxetic effects are found to be governed by different structural features.